Flash spark plasma sintering of ultrafine yttria-stabilized zirconia ceramics. (August 2016) - Vasylkiv, Oleg; Borodianska, Hanna; Sakka, Yoshio; Demirskyi, Dmytro
Abstract: The microstructure evolution during high heating rate 'flash' spark plasma sintering (SPS) of ultrafine yttria-stabilized zirconia powder is presented. Consolidation during SPS took place in a single-stage, the activation of preferable interaggregate densification, and thus preserving microstructural features of initial powder. Different sintering stages were identified during conventional SPS, showing a distinctive role of processing temperature. An explanation and analysis of the driving forces behind these observations was attempted. Graphical abstract: